Analysis Of Cough And Analgesic Range Of Pharmaceutical Active Ingredients Using Rp-Hplc Method - USENI REDDY MALLU; VARAPRASAD BOBBARALA; SOMASEKHAR PENUMAJJI (International Journal of Pharma and Bio Sciences, 2011)
A novel and single RP-HPLC method was developed for the determination of ten active ingredients (Codeine phosphate, Paracetamol, Chloropheniramine Maleate, Theophylline, Pseudoepidrine HCl, Ambroxol, Salbutamol, Guaiphenesin, Dextromethorphan and Diphenhydramine HCl) in all pharmaceutical dosage forms, along with preservative (Sodium benzoate) and validated the method as per ICH and FDA guidelines. The separation was achieved on a X-Terra C18, 15cm x 4.6mm, 3.5 µ in the simple gradient mode using Sol-A: buffer and Sol-B: Acetonitrile (0-5min, sol-A:97-97; 5-10min- sol-A:97-92; 10-15min- sol-A:92-68; 15-23min- sol-A:68-68; 23-25min- sol-A:68-97 and 25-30min- sol-A:97-97) with 0.8 mL per min flow rate. Column oven temperature maintained at 40°C and performed the analysis with 220 nm. Quantification was achieved with 40µg per mL for all ingredients with 100±3.0% recovery. The method was validated by determining its sensitivity, linearity, accuracy and precision. The proposed method is single, shorter runtime, accurate and reproducible. This method can be applied for routine analysis of all ten active ingredients quantification in all pharmaceutical dosage forms.